IN VIVO ANALYSIS OF THE EFFECT OF NANOSTRUCTURED LIPID CARRIER-BASED GEL OF MULBERRY ROOT EXTRACT AGAINST ULTRAVIOLET LIGHT - Faizatun, Faizatun; Anwar, Effionora; Merdiyah, Liza Indah (International Journal of Applied Pharmaceutics, 2018)
Objective: This study aimed to analyze the in vivo anti-ultraviolet (UV) activity of nanostructured lipid carrier (NLC) of mulberry extract on six New Zealand rabbits. Methods: Mulberry roots were treated with 96% ethanol using a maceration-ultrasonication method, and the extract was transformed into NLCs using the solvent evaporation method. The NLC was characterized for particle size and polydispersity index and zeta potential. The morphology of nanoparticles was examined using transmission electron microscope and subsequently in the NLC-based gel preparation. The gel was evaluated in vivo for anti-UV activity on male rabbits in three treatment groups: Positive control, sample gel, and negative control (exposed to UV light for 6 h). The anti-UV activity was scored as a skin erythema response using Dermalab®, and the results were analyzed using Kruskal–Wallis and Mann–Whitney methods. Results: The particle size, polydispersity index, and zeta potential of the NLC were quantified as 203.2 nm, 0.264, and −38.7 mV, respectively. The viscosity of the gel was 42,500 cps, with pseudoplastic thixotropic flow properties including the spreading ability, particle size 5156.81 mm, and pH 5.92, respectively. The anti-UV activity was determined as 0.22, 1.44, and 2.22 for the positive control, NLC-based gel, and negative control groups, respectively. Conclusion: The anti-UV activity of NLC-based gel of mulberry root extract was very small on areas where erythema had formed and differed significantly between the positive and negative control groups (p<0.05).